"What's Disability Got to Do With It?" Examining Ability Privilege in a Disability Studies Course. Issue 1 (2nd January 2017) - Bialka, Christa S.; Morro, Danielle
Abstract: Although much research addresses prejudice toward and discrimination of individuals with disabilities, few studies engage with the concept of ability privilege, or the benefits that typically abled individuals are afforded in relation to their position within the hegemony. Given the fledgling nature of research on ability privilege, it is both useful and necessary to examine how and where this construct might be discussed. The purpose of this qualitative case study was to explore how undergraduate students in an introduction to disability studies course, premised on a social justice orientation, engaged with ability privilege. Findings revealed that coursework and related partnerships provided participants with exposure to ability privilege, and participants utilized the constructs of ableism, rhetoric, and accessibility in order to recognize advantages they were afforded on account of their ability status. The results of this study have direct significance in aiding the design of coursework that pushes students to engage with their ability privilege. Moreover, this study endeavors to contribute to and extend upon nascent conversations related to this construct.